EKSISTENSI DAN ADAPTASI GRUP BAND THRASH METAL DAN ROCK DI NEGERI SYARIAT - Pardian Saputra (Aceh Anthropological Journal, 2018)
Fatwa ulama no. 12 of 2013 on Art and Culture of Other Arts in Islamic Syariat in Banda Aceh, should the band with the rock music genre not be able tosurvive for long periods in ‘Aceh. But in reality bands of music genre Thrash Metal and Rock is still survive and present with real in public space in Aceh. This study looks at how the development, existence, and adaptation of the bands Inverno and Cronic in Banda Aceh. The Cronic band was formed in 1999, while Inverno was formed in 2011 in Banda Aceh. From interviews with the band Cronic and personnel about the existence and adaptation Inverno they found that the factors that affect their existence among other ways, through their consistency in the work and the support they received from various parties. he adaptations performed by Cronic and Inverno bands are through the adjustment of lyrics and the meaning of the song lyrics on the albums and singles that they release and make adjustments in terms of the outfit used when they concert as well as the theme song selection of each of their works